Sex differences in the effects of 12 weeks sprint interval training on body fat mass and the rates of fatty acid oxidation and VO(2)max during exercise - Bagley, Liam (BMJ Open Sport Exerc Med, 2016)
BACKGROUND: The purpose of this study was to examine whether very short duration, very high intensity sprint interval training (SIT) leads to loss of body fat mass in association with improvements to VO(2)max and fatty acid oxidation, and to assess the extent of sex dimorphism in these physiological responses. METHODS: A total of 24 men and 17 women (mean (SEM) age: 39 (±2) years; body mass index 24.6 (0.6)) completed measurements of the maximal rate of oxygen uptake (VO(2)max) and fatty acid oxidation (FATmax). Body fat and lean mass were measured by dual emission x-ray absorptiometry, and fasting blood lipid, glucose and insulin profiles were assessed before and after training. SIT consisted of 4×20 s sprints on a cycle ergometer at approximately 175% VO(2)max, three times per week for 12 weeks. RESULTS: Fat mass decreased by 1.0 kg, although men lost statistically significantly more fat than women both when expressed in Kg and as % body fat. VO(2)max increased by around 9%, but women improved VO(2)max significantly more than men. FATmax improved by around 13%, but fasting plasma glucose, insulin, total triglyceride, total cholesterol and high-density lipoprotein (HDL) did not change after training, while low-density lipoprotein decreased by 8% (p=0.028) and the HDL:Total Cholesterol ratio improved by 6%. There were no sex differences in these metabolic responses to training. CONCLUSIONS: These results show lower body fat %, and higher rates of fatty acid oxidation and VO(2)max after 12 weeks of training for just 4 min per week. Notably, women improved VO(2)max more than men, while men lost more fat than women.